An IQSEC2 Mutation Associated With Intellectual Disability and Autism Results in Decreased Surface AMPA Receptors - Rogers, Eli J.; Jada, Reem; Schragenheim-Rozales, Kinneret; Sah, Megha; Cortes, Marisol; Florence, Matthew; Levy, Nina S.; Moss, Rachel; Walikonis, Randall S.; Palty, Raz; Shalgi, Reut; Lichtman, Daniela; et al. (Frontiers in Molecular Neuroscience, 2019)
We have recently described an A350V mutation in IQSEC2 associated with intellectual disability, autism and epilepsy. We sought to understand the molecular pathophysiology of this mutation with the goal of developing targets for drug intervention. We demonstrate here that the A350V mutation results in interference with the binding of apocalmodulin to the IQ domain of IQSEC2. We further demonstrate that this mutation results in constitutive activation of the guanine nucleotide exchange factor (GEF) activity of IQSEC2 resulting in increased production of the active form of Arf6. In a CRISPR generated mouse model of the A350V IQSEC2 mutation, we demonstrate that the surface expression of GluA2 AMPA receptors in mouse hippocampal tissue was significantly reduced in A350V IQSEC2 mutant mice compared to wild type IQSEC2 mice and that there is a significant reduction in basal synaptic transmission in the hippocampus of A350V IQSEC2 mice compared to wild type IQSEC2 mice. Finally, the A350V IQSEC2 mice demonstrated increased activity, abnormal social behavior and learning as compared to wild type IQSEC2 mice. These findings suggest a model of how the A350V mutation in IQSEC2 may mediate disease with implications for targets for drug therapy. These studies provide a paradigm for a personalized approach to precision therapy for a disease that heretofore has no therapy.